Full-Length Transcriptome Sequencing Reveals the Molecular Mechanism of Metasequoia glyptostroboides Seed Responding to Aging - Yongjian Luo; Yixin Zhang; Jingyu Le; Qing Li; Jiaolin Mou; Shiming Deng; Jitao Li; Ru Wang; Zhijun Deng; Jun Liu (MDPI AG, 2023)
Metasequoia glyptostroboides, Hu and W. C. Cheng, as the only surviving relict species of the Taxodiaceae Metasequoia genus, is a critically endangered and protected species in China. There is a risk of extinction due to the low vigor of M. glyptostroboides seeds, and the physiological mechanism of seed aging in M. glyptostroboides is not yet clear. In order to investigate the physiological and molecular mechanisms underlying the aging process of M. glyptostroboides seeds, we analyzed the antioxidant system and transcriptome at 0, 2, 4, 6, and 8 days after artificial accelerated aging treatment at 40 °C and 100% relative humidity. It was found that the germination percentage of fresh dried M. glyptostroboides seeds was 54 ± 5.29%, and significantly declined to 9.33 ± 1.88% after 6 days of aging, and then gradually decreased until the seed died on day 8. Superoxide dismutase (SOD) activity, ascorbic acid (AsA), glutathione (GSH) content and superoxide anion (O2·−) content and production rate significantly decreased, while malondialdehyde (MDA) and hydrogen peroxide (H2O2) content and glutathione peroxidase (GPX) and catalase (CAT) activity gradually increased during the aging process. A total of 42,189 unigenes were identified in the whole transcriptome, and 40,446 (95.86%) unigenes were annotated in at least one protein database. A total of 15,376 differentially expressed genes (DEGs) were obtained; KEGG enrichment analysis results revealed that seed aging may be mainly involved in the protein-processing pathways in endoplasmic reticulum, oxidative phosphorylation, and ascorbate and aldarate metabolism. Weighted gene co-expression network analysis (WGCNA) revealed that the dark magenta, orange, and medium purple modules were highly correlated with physiological indicators such as SOD, CAT, and GSH and further identified 40 hub genes such as Rboh, ACO, HSF, and CML as playing important roles in the antioxidant network of M. glyptostroboides seeds. These findings provide a broader perspective for studying the regulatory mechanism of seed aging and a large number of potential target genes for the breeding of other endangered gymnosperms.